PATH-09. THE SEARCH FOR A NOVEL SUBTYPE OF GLIOBLASTOMA AND ITS CELL-OF-ORIGIN. (12th November 2021) - Chen, Yu-Jung; Iyer, Swathi; Xie, Xuanhua; Parada, Luis
Abstract: Glioblastoma (GBM) has been computationally classified into three molecular subtypes (i.e., classical, proneural and mesenchymal). However, these subtypes lack strong biological and clinical implications. Therefore, our group has proposed to classify GBM according to its cell of origins. We have previously shown that different cell of origins give rise to biologically and transcriptionally distinct subtypes of GBM. We termed tumors that derived from subventricular zone (SVZ) neural stem cells as type 1 tumors and that from oligodendrocytic progenitor cells (OPC) as type 2 tumors. Based on murine lineage transcriptional profiles, we have also identified corresponding human GBM (40-50% of the TCGA GBM samples) tumors with conserved lineage properties. However, a majority of the TCGA GBM tumors remains unexplained by the cell-of-origin model. This study aims to search for other distinct GBM subtypes by addressing the tumorigenic potential of a putative stem progenitor population in the murine basilar pons. By using a recently reported Nestin transgenic mouse line (Nestin-C reERT2; eG FP-H2B; hD TR, or CGD in short), we have shown that conditionally deleting the commonly mutated glioma genes, Nf1 f/f ; Tp53 f/f and Pten f/+ ( NPP ), in pontine GFP + cells, give rise to tumors that histologically resembles human GBM. Further transcriptomic analysis showed that a subset of these tumors highly express lineage markers of the differentiation-committed oligodendrocytic precursors (COP). We further probed the TCGA GBM database and identified 5% of the tumors to be enriched with our CGD pontine tumor-derived signature. In summary, our results showed that CGD-NPP cells can give rise to a previously uncharacterized tumor subtype with enrichment of COP lineage markers. Therefore, we propose COP as another cell of origin for GBM and that COP-derived tumor may contribute to a novel tumor subtype of the GBM classification.